2009
DOI: 10.1002/uog.6275
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester maternal serum tumor necrosis factor receptor‐1 and pre‐eclampsia

Abstract: Objectives To examine whether the maternal serum concentration of the soluble receptor-1 of tumor necrosis factor-α (TNF-R1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 39 publications
0
21
0
2
Order By: Relevance
“…Although 65 combinations of markers included at least 1 marker that was assessed during the second trimester, only 6 combinations included both biological and ultrasonographic markers measured during the first trimester (32)(33)(34)(35)(36)(37). No given combination was assessed more than once.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 65 combinations of markers included at least 1 marker that was assessed during the second trimester, only 6 combinations included both biological and ultrasonographic markers measured during the first trimester (32)(33)(34)(35)(36)(37). No given combination was assessed more than once.…”
Section: Discussionmentioning
confidence: 99%
“…When these variables were combined in logistic regression algorithms for early PE, a predictive rate of 94% at a false-positive rate of 5% was observed (35 ). Therefore, a growing body of evidence suggests that combination of first-trimester biochemical and ultrasonographic markers may be useful in prediction of early PE; the addition of maternal characteristics to the prediction algorithms might further improve their performance (33,(35)(36)(37). Although regression analysis demonstrated significant contribution to the detection or PE from maternal factors, TNF-R1, and PI, in multiple regression analysis, there was no significant contribution of TNF-R1 (P ϭ 0.07) to the prediction provided by maternal factors and PI (sensitivity 32%, specificity 95%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TNFreceptors are useful in first-trimester screening of women who are at subsequent risk of preeclampsia. 63,64 By contrast, elevated levels of TNF-R1 and TNF-R2 have been described as markers of normal human pregnancy, although a lack of soluble TNF-receptors have been associated with spontaneous miscarriage in women who undergo recurrent miscarriage. 65 In our study, there was significantly higher TNF-R1 levels in the plasma of patients with TM who had a normal pregnancy.…”
Section: Wwwajogorgmentioning
confidence: 99%
“…While certain studies report increased TNF-α or TNF-R1 levels at as early as the first trimester in patients who subsequently develop preeclampsia, others reveal no significant difference between preeclampsic patients and controls (27,28). Leal et al found that maternal serum TNF-R1 levels at 11-13 weeks gestational age was increased in pregnant subjects developing preeclampsia, but the TNF-R1 levels were not associated with the degree of impairment in placental perfusion or the severity of preeclampsia (29). Our findings were consistent with the above-mentioned studies and supported the hypothesis that intravascular inflammation is a mechanism of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%